Identification of Socio-Demographic Factors with the Incidence of Stunting in Elementary School Children in Rural Enrekang - Abri, Nur (Media Publikasi Cendekia Indonesia, 2022)
Objective: Stunting is a major health emergency in most developing countries, including Indonesia. The total number of stunting children in 2019 in Enrekang Regency is quite high at 44.8%. Therefore, this study aims to determine the relationship between maternal knowledge, maternal education level, and the number of family members with the incidence of stunting in elementary school children in rural Enrekang, South Sulawesi. Method: An analytical observational study with a cross sectional approach. The subjects of the study were the mother and her child aged 6-12 years. Data collection using microtoa and questionnaires. 100 total samples were collected based on purposive sampling method. Data analysis using chi-square. Results: This study shows the proportion of stunted children 72.0%, maternal knowledge less 90.0%, low maternal education 66.0%, family size 95.0%. The results of statistical tests showed a significant relationship between maternal knowledge (p = 0.027) and the incidence of stunting. Meanwhile, the level of maternal education (p = 0.992) and the number of family members (p = 0.919) are not related to stunting events. Conclusion: There is a significant relationship between maternal knowledge and stunting events. Increasing health knowledge and nutritional awareness in mothers through health promotion, stunting education with posters and the distribution of leaflets on sustainable stunting is a toll road in tackling chronic nutrition in children in rural Enrekang